Business Inventory Management System for Alfudullallah Co - Asim, Ibrahim; ARBAIY, NUREIZE (Applied Information Technology And Computer Science, 2026)
An essential indicator of a company’s inventory management system is its inventory management effectiveness. Inventory management ensures that goods are available to meet customer demand while reducing expenses associated with inventory storage, storage and disposal. Many businesses still need help implementing an effective inventory system for various reasons. Companies that rely solely on manual stock management techniques have experienced problems such as inaccurate stock levels and long replenishment delays. Therefore, this project aims to improve the effectiveness of Alfudullallah Co.’s inventory operations by building an Inventory Management System (IMS). Although the company uses a manual method to manage its inventory, it sells various products. When the number of items increases, there are difficulties in efficiently managing stock levels and meeting the demands of its clients. Hence, the new system is built to provide real-time inventory tracking and handle inventory management to reduce manual errors. The prototype method is utilised during system development. PHP and MySQL are used for programming. Several modules are provided in the newly developed system, such as inventory, warehouse, ordering, report and analysis management. Alfudullallah Co. will ensure that products are available on time and improve customer satisfaction by providing these processes.